CONNECTING ENGLISH LANGUAGE TEACHING WITH 12 BRAIN/MIND LEARNING PRINCIPLES - Jorge Correa Rodriguez (IJIET (International Journal of Indonesian Education and Teaching), 2018)
On a daily basis, teachers all over the world modify their students brain when they teach the contents that the students need to learn; this biological, cognitive and behavioral process is called learning. From a biological, cognitive and educational point of view, those modifications are totally necessary for the development of the learners. One of those so called brain-modification experiences occurs when they learn English. Then, you may wonder, how could these modifications (learning) be enhanced? In order to answer this question, this paper suggests a connection between 12 brain/mind learning principles(Caine, Caine, Klimek, McClintic, 2009) and English teaching aiming to make it more effective. The reason for this connection is that if teachers become aware of the way the brain learns, their practices may be enhanced leading to more effective teaching and learning (Geake, 2009). Thus, in order to state this connection, every principle is presented, described and followed by some general practical suggestions related to English teaching. It is necessary to mention that all the included suggestions will be simply examples; it would be then the task of the reader, the teacher or instructor, to ignite her creativity by applying the principles in her particular context to enhance her teaching practices and promote English language learning among students.DOI:https://doi.org/10.24071/ijiet.2018.020208